The Use of Dialog to Build Scientific Literacy in the Laboratory Setting - Jacox, Richard (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Students that are scientifically literate demonstrate the ability to use verbal descriptions, pictorial representations, the language of mathematics, and technology applications to build conceptual models of natural phenomena that are useful both for describing observations and making predictions based on observed behavior. The laboratory setting is ideal for the use of classroom dialog that emphasizes invitational questioning to identify student preconceptions, gently expose misconceptions, and help students extend their understanding in ways that enable them to reconceptualize their prior knowledge base. A framework for designing the laboratory experience emphasizing invitational questioning and conversational interaction, rather than passive, recipe-based laboratory experiences, integrating as many of the four domains of scientific literacy as possible in a safe, is proposed in this manuscript.